The UCEA Project on Education Leadership: Voices from the Field, Phase 3 - Michele Acker-Hocevar; Teresa Northern Miller; Gary Ivory (Educational Considerations, 2009)
This special issue of Educational Considerations is devoted to the national research study "Voices from the Field: Phase 3" (hereafter referred to as Voices 3), conducted by the University Council for Educational Administration (UCEA) to study the perceptions of superintendents and principals regarding school improvement, social justice, and democratic community.
Keywords: Education; leadership; voices; phase; participation; American Association of School Administrators AASA